FEATURES OF THE PROLIFERATIVE ACTIVITY OF WELL DIFFERENTIATED AND POORLY DIF-FERENTIATED SQUAMOUS CELL LUNG CANCER - Proskurnya, S.A.; Sovhyria, S.M.; Filenko, B.N.; Royko, N.V. (World of Medicine and Biology, 2017)
According to the World Health Organization classification, one of the modifications of the epithelial tumors of the lungs is squamous cell cancer, which has different degrees of differentiation that directly influences the effectiveness of treatment and further prognosis for the disease. The paper was aimed at the study of the histological features and diagnostic significance of the immunohistochemical Ki-67 proliferation marker in squamous cell lung cancer of different degrees of differentiation. To achieve the objective of the investigation, we used surgical and biopsy material of 50 patients with squamous cell lung cancer. Primary monoclonal antibodies to the Ki-67 (SP6 clone, LabVision) have been used for immunohistochemical study. Positive immunohistoche-mical reaction with antibodies to the Kі-67 has been revealed with the brown coloring of cell nuclei of varying intensity. The investigation showed a general pattern of the Kі-67 proliferation marker expression in the squamous cell lung cancer. High proliferative activity has been observed in the tumoral complexes of poorly differentiated squamous cell lung cancer, which is characterized by the intranuclear expression of 48% to 95% of the cells. The lowering of the cells’ ability to mitosis is changing in the direction of acquiring the citodifferential signs, revealed by the insignificant expression of the Kі-67 marker in 5-20% of the cells.